Analisis Strategi dan Tindak Tutur Direktif Masyarakat di Pesisir Pantai dalam Komunikasi - Minto, deriwan (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
There is an assumption that coastal communities tend to speak loudly, loudly and without further ado. Communication can fail to understand if not addressed properly. The aim of the research was to specifically describe the strategies and speech acts to direct the people on the coast in communication. This type of qualitative research, descriptive analysis approach. Observation data collection techniques, recording and recording. Validity is semantic validation. The analysis was carried out reducing, presenting and drawing conclusions. Based on the research results, 59.86% or more than half communicated more to ask questions. Communication by "asking" too much can have an effect that is not good. Directive communication strategies were found in 70.95% of the group with pleasantries but with positive politeness. This means that if coastal communities communicate only their voices are louder and tend to be louder. However, if analyzed specifically from the utterances spoken they tend to be polite.